Racialism Slavery As Reflected In Paul Laurence Dunbar’s Poems To Social Life - Narlius Reinal Erianto (Jurnal Ilmiah Langue and Parole, 2017)
Slavery to Social life's Racialism analyzes the disclosure of a black-life tragedy of slavery and racism in their social life. The author takes data from Dunbar's poems: We Wear the Mask, The Debt, Sympathy, Life's Tragedy and The Paradox. In these five poems the author analyzes how slavery that has taken place in America on the basis of the five poems of Dunbar, some kind of racism that the author finds in the five poems of Dunbar, and the result of social slavery to the black social life in America that the author finds in The five poems of Dunbar. This research method is descriptive qualitative, which try to explain about correlation between writer life background which pour through poetry and its influence to human social life. In analyzing the five poems of Dunbar, the author uses a psychological approach that discusses the psychology of human personality which is the theory of Sigmund Freud including the id, ego, and the human superego. The main source of data obtained from the five poems Dunbar namely: We Wear the Mask, The Debt, Sympathy, Life's Tragedy and The Paradox. Other sources come from articles and internet books. From the analysis of the five poems of Dunbar, the authors found that (1) Slavery and human rights abuses against blacks in America are reflected through the five poems of Dunbar. (2) The author finds some form of racism such as the occurrence of discrimination and persecution that caused the suffering of blacks in America on the basis of the fifth poems of Dunbar and (3) There have been proven consequences of the slavery experienced by blacks in America that the author has discovered from the fifth Dunbar's poetry is like feeling oppressed or experiencing the mental stress that causes blacks in America to suffer.